Cinnamyl alcohol dehydrogenases‐C and D, key enzymes in lignin biosynthesis, play an essential role in disease resistance in Arabidopsis - TRONCHET, MAURICE (Mol Plant Pathol, 2009)
The deposition of lignin during plant–pathogen interactions is thought to play a role in plant defence. However, the function of lignification genes in plant disease resistance is poorly understood. In this article, we provide genetic evidence that the primary genes involved in lignin biosynthesis in Arabidopsis, CAD‐C and CAD‐D, act as essential components of defence to virulent and avirulent strains of the bacterial pathogen Pseudomonas syringae pv. tomato, possibly through the salicylic acid defence pathway. Thus, in contrast with cellulose synthesis, whose alteration leads to an increase in disease resistance, alteration of the cell wall lignin content leads directly or indirectly to defects in some defence components.